CSR by Islami Bank in healthcare stakeholders’ perception - Rahman, Shafiqur; Jahan, Sadia; McDonald, Nicholas (Bangladesh Journal of Medical Science, 2010)
Background: In the Bangladesh society, a few organizations are contributing through their activities on Corporate Social Responsibility (CSR). It is a general belief that the contribution of Islami Bank Bangladeshi Limited in CSR is highest among the financial institutions. It is an observation that IBBL's CSR contribution in the healthcare sector is very significant. Objective: This paper explores the stockholders' perception of CSR contribution in the healthcare sector by Islami Bank Bangladesh Limited (IBBL). Method: Authors used qualitative approach in doing the research. Data were collected through a survey. Likert scale was used to explore the significance of stakeholders' perception. Results: This paper reports the findings of a qualitative study on perceptions of CSR by IBBL in the healthcare sector of a heterogeneous group of stakeholders. The findings reveal the perception of stakeholders towards the social contribution of Islami Bank Central Hospital (IBCH), an Institution for CSR in healthcare by IBBL. The stakeholders believe that this hospital is significantly contributing to the society through its support in the healthcare sector. It is also found that the hospital is proactive in providing healthcare support to the community through its highly standard human resources, world class medical equipment, outstanding management team and superb customer care support. Conclusion: This exploratory study makes a contribution to the relatively new body of work on CSR in Bangladesh, especially in the healthcare sector by IBBL and hopefully will encourage further research on the topic. This study will also contribute to improve the governance, social, ethical, and environmental conditions of the healthcare sector. Key words: Corporate Social Responsibility (CSR); healthcare sector; stakeholders' perception. DOI: 10.3329/bjms.v9i4.6687 Bangladesh Journal of Medical Science Vol.09 No.4 July 2010 pp.208-215